Catchment management agencies for poverty eradication in South Africa - Schreiner, B.; van Koppen, Barbara (2002)
This paper discusses the changes in water law in South Africa since the new dispensation. The focus is on the poverty dimensions of the early experiences of implementation of one of the components of the National Water Act: the establishment of Catchment Management Agencies. From a diversity of recent experiences in decentralizing integrated water resources management, key areas emerge where future actions by the government are crucial to establish pro-poor, developmental catchment management Agencies.